Discovering the nanoscale origins of localized corrosion in additive manufactured stainless steel 316L by liquid cell transmission electron microscopy. (November 2022) - Tian, Mengkun; Choundraj, Jahnavi Desai; Voisin, Thomas; Wang, Y. Morris; Kacher, Josh
Abstract: We use liquid cell scanning transmission electron microscopy (STEM) to directly characterize the nanoscale origins of corrosion initiation in Additive manufacturing (AM) 316 L stainless steel. Under applied anodic potentials, we found that the dislocation cellular boundaries were preferentially corroded and that regions of localize corrosion occurred along the cellular boundaries. We directly observed the earliest stages of corrosion by controlling the biasing parameters to decelerate the corrosion processes. The results show that highly localized corrosion occurs via inclusion dissolution along dislocation cell boundaries. More widespread corrosion initiates at the dislocation cell boundaries and spreads throughout the dislocation networks. Graphical Abstract: ga1 Highlights: Use TEM to study the corrosion of AM 316 L stainless steel in a liquid cell holder. Dislocation cellular boundaries were preferentially attacked. Dissoluion of inclusion occured at the cellular boundaries.